Analisis Yuridis Atas Akta Notaris Yang Cacat Hukum Dan Implikasinya Terhadap Kepastian Hukum - Teresa P. Sapni , Dripsy (Magister Kenotariatan, Universitas Jambi, 2025)
Notaries have an important role in ensuring legal certainty through the creation of authentic deeds. However, in practice, there are various cases where deeds made by notaries contain legal defects, resulting in cancellation or cancellation by law by the court. This study aims to analyze the factors causing legal defects in notarial deeds, the form of notary accountability, and its legal enforcement against the parties. This study uses a qualitative method with a normative legal approach, by reviewing regulations, scientific journals, and related court decisions. The results of the study indicate that notaries can be held accountable for both civil, administrative, and criminal, depending on the level of error made. In addition, deeds containing legal defects have the potential to cause legal uncertainty and losses for the parties involved. Therefore, stricter supervision of notarial practices and increased notary professionalism are needed, so that cases of legal defects in deeds can be minimized.